A pilot study of a longitudinal mindfulness curriculum in undergraduate medical education (Canadian Medical Education Journal, 2020)
Background: To support student well-being, a mindfulness curriculum in undergraduate medical education was launched at our university in 2014. We describe the program and report 3-year results.Methods: Medical students responded to online questionnaires on mindfulness (Freiburg Mindfulness Inventory), empathy (Jefferson Scale of Physician Empathy), resilience (Connor-Davidson Resilience Scale) and perceived stress (Perceived Stress Scale) and were surveyed for demographics, home practice, and subjective experience at curriculum launch and yearly for 3 years.Results: In respondents, high stress (19.2 (SD=6)) and low resilience (71.2 (SD=12.5)) scores were seen throughout training. Scores for mindfulness correlated positively with those for empathy (r=.217 p